The Effect of Teaching Cooking Skills to Parents on Health Status of Children and Adolescents: A Systematic Review - Seyed Mohammad Mehdi Hazavehei; Malihe Taheri; Samaneh Shirahmadi; Nafise Rezaei (Hamadan University of Medical Sciences, 2015)
Background & Objectives: The present systematic review investigated and analyzed interventions in the field of parental skills in cooking healthy food in order to identify the most effective training methods to create a lasting and positive effect on the implications of health promotion of children and adolescents. Materials and Methods: Electronic search of databases was performed using the key words in English and Persian from Scopus, Proquest, Science Direct, Pub Med, Springer, Biomed Central, Google Scholar, Iran Medex and SID. The inclusion criteria were all educational interventions that included cooking healthy food with the aim to increase knowledge and skills of parents, or to assess the impact of interventions on children and adolescents, and that were published between January 2005 and September 2014. Results: Cooking skills educational interventions for parents were divided into two types 1: based on health education models and theories, and 2: without using health education models and theories. Among the seven articles reviewed, four studies were classified in the first group and three in the second group. The studies were compared based on changes in body mass index as well as the persistence of behavior change in the subsequent follow-ups. Conclusion: Use of multi-component education and follow-up that apply theories and models of health education are effective to reach the expected results. Clinical trials with several long-term strategies are required to create a favorable change in body mass index of children and teens.